Design, construction, performance evaluation and economic analysis of an integrated collector storage system - Kalogirou, Soteris A. (My University, 1997)
The design and construction of an Integrated Collector Storage (ICS) system is presented in this paper. The main advantage that such a collector system presents, with respect to conventional flat-plate collectors, is the fact that it is of a very low profile. The main disadvantage of these collectors comes from the design of the system, i.e. with the receiver of the collector being also the storage vessel, it is not possible to insulate it properly and there are significant heat losses during the night. System modelling and optimisation is carried out by the use of a computer code written for the purpose. Performance results presented are in good agreement with the predicted results, especially for the end-of-day storage temperature which is predicted to within 5.1%. The initial cost of the system presented here is 13% cheaper than the corresponding flat-plate (FP) collector of the same aperture area and storage volume. Additionally, the economic analysis of the two systems, performed with the F-Chart program, showed a yearly F-value of 0.85 for the ICS system compared to 0.83 for the FP system, a pay-back period of nine years for the ICS system, compared to 11 years for the FP system and a life cycle saving of C£330 for the ICS system compared to C£201 for the FP system.
Keywords: Integrated Collector Storage (ICS) system